2021
DOI: 10.1126/science.abf7258
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the CGRP receptor in apo and peptide-bound forms

Abstract: G protein-coupled receptors (GPCRs) are key regulators of information transmission between cells and organs. Despite this, we have only limited understanding of the behavior of GPCRs in the apo state and the conformational changes upon agonist binding that lead to G protein recruitment and activation. We expressed and purified unmodified apo and peptide-bound calcitonin gene-related peptide (CGRP) receptors to determine their cryo-EM structures and complemented these with analysis of protein conformational dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 53 publications
(125 reference statements)
3
66
0
Order By: Relevance
“…The current study focuses on the mechanism of binding for the N-terminal domain of CGRP that is critical to activation of CGRPR. Recent work elucidated the structures of apo and peptide-bound CGRPR in the absence of transducer protein ( Josephs et al, 2021 ) and revealed that, as expected, the peptide C-terminus is stably engaged with the ECD of the receptor, albeit that the ECD is highly dynamic. However, the N-terminus of the peptide only transiently engages with the core of the receptor.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…The current study focuses on the mechanism of binding for the N-terminal domain of CGRP that is critical to activation of CGRPR. Recent work elucidated the structures of apo and peptide-bound CGRPR in the absence of transducer protein ( Josephs et al, 2021 ) and revealed that, as expected, the peptide C-terminus is stably engaged with the ECD of the receptor, albeit that the ECD is highly dynamic. However, the N-terminus of the peptide only transiently engages with the core of the receptor.…”
Section: Resultsmentioning
confidence: 72%
“…The gradual engagement of the top of TM6, TM7 and ECL3 by the peptide N-terminal domain was accompanied by an inward movement of ECL3 ( Supplementary Video S1 ); ECL3 is important for CGRPR signaling ( Barwell et al, 2011 ) but its dynamics during receptor activation are still unclear. A comparison between the consensus maps of CGRP:CGRPR and CGRP:CGRPR:G s complexes ( Josephs et al, 2021 ) shows that the location of the top of TM6/7/ECL3 in the former structure partially overlaps with the location of the peptide binding pocket in the active CGRPR. Analysis of the conformational dynamics of the CGRP:CGRPR complex revealed that the top of TM6/7/ECL3 dynamically opens and closes in association with transient interaction of the peptide N-terminus and the TMD core ( Josephs et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations